Stability in Artificial Intestinal Fluid of Mangosteen Peel Extract Nanoencapsulation Cross-Linking Chitosan With Sodium Tripolyphosphate - Andri Kusmayadi; Richa Mardianingrum; Yanti, Yanti (Universitas Muhammadiyah Malang, 2026)
The ratio of the protective walls has a major effect on the stability of the resulting nanocapsules. The purpose of the study is to investigate the formulation and characterization of mangosteen peel extract nanoencapsulation (MPEN) utilizing chitosan cross-linked with STPP in various ratios to stability in artificial intestinal fluid (AIF). Mangosteen peel was extracted using ethanol and maceration method. The ionic gelation process was used to synthesize MPEN. Mangosteen peel extract (MPE), chitosan solution, and STPP were combined to generate MPEN. Chitosan and STPP have the following ratios: 1:1, 2:1, 3:1, 4:1, and 5:1. The mechanism of the ionic gelation interaction between chitosan and STPP occurs through gel formation via ionic bonds between the positive charge of chitosan and the negative charge of STPP. The results showed that the ratio of chitosan:STPP had a significant effect (P<0.05) on the stability of nanocapsules. The use of chitosan:STPP ratio at levels 1:1 to 4:1 (T1 - T4) was able to increase the stability value to 90.309% - 90.765%. While the ratio of 5:1 produced the lowest stability value of only 89.990%. The chitosan:STPP ratio at a balanced level of 1:1 is recommended as the optimal ratio to increase the stability values.